2013
DOI: 10.1007/978-3-642-42033-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Four-Dimensional GLV via the Weil Restriction

Abstract: Abstract. The Gallant-Lambert-Vanstone (GLV) algorithm uses efficiently computable endomorphisms to accelerate the computation of scalar multiplication of points on an abelian variety. Freeman and Satoh proposed for cryptographic use two families of genus 2 curves defined over Fp which have the property that the corresponding Jacobians are (2, 2)-isogenous over an extension field to a product of elliptic curves defined over F p 2 . We exploit the relationship between the endomorphism rings of isogenous abelian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…In the case of binary GLS elliptic curves, Oliveira et al [35] report the implementation of a curve exploiting the 2-GLV method. More recently, Guillevic and Ionica [18] show how to exploit the 4-GLV method on certain genus one curves defined over F p 2 and genus two curves defined over F p ; and Smith [39] proposes a new family of elliptic curves that support 2-GLV decompositions.…”
Section: The Glv and Gls Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of binary GLS elliptic curves, Oliveira et al [35] report the implementation of a curve exploiting the 2-GLV method. More recently, Guillevic and Ionica [18] show how to exploit the 4-GLV method on certain genus one curves defined over F p 2 and genus two curves defined over F p ; and Smith [39] proposes a new family of elliptic curves that support 2-GLV decompositions.…”
Section: The Glv and Gls Methodsmentioning
confidence: 99%
“…Later, in [16] Galbraith et al showed how to exploit the Frobenius endomorphism to enable the use of the GLV approach on a wider set of curves defined over the quadratic extension field F p 2 . Since then, significant research has been performed to improve the performance [30,24] and to explore the applicability to other settings [20,35] or to higher dimensions on genus one curves [24,31,18] and genus two curves [8,9,18]. Unfortunately, most of the work and comparisons with other approaches have been carried out with unprotected algorithms and implementations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the advantages to make the scalar multiplication regular (one doubling and one addition per scalar bit) and to reduce the storage requirement as only the points P and P + φ(P ) need to be stored. The GLV method has later been extended to a larger set of curves defined over F p 2 [14,32,19,27] which are endowed by more than one endomorphism. In this case additional performance gains can be achieved, whereas it implies the need of more memory.…”
Section: Curve With Efficient Endomorphismmentioning
confidence: 99%
“…Combinations of ρ and ψ may be used for four-dimensional scalar decompositions; for example, the endomorphisms [1], ρ, ψ, ρψ can be used as a basis for the 4-dimensional decomposition techniques elaborated by Longa and Sica in [18]. In fact, reducing these CM fibres modulo a well-chosen p turns out to form a simple alternative construction for some of the curves investigated by Guillevic and Ionica in [14]: the twisted curve E From the point of view of scalar multiplication, using CM fibres of these families allows us to pass from 2-dimensional to 4-dimensional scalar decompositions, with a consequent speedup. However, in restricting to CM fibres we also re-impose the chief drawback of GLV on ourselves: that is, as explained in the introduction, we cannot hope to find secure (and twist-secure) curves over F p 2 when p is fixed.…”
Section: Degree One: Gls As a Degenerate Casementioning
confidence: 99%